Arenaceous Foraminifera from Ordovician and Silurian limestones of Oklahoma - Moreman, W. L. (Journal of Paleontology, 1930)
Thirteen genera and thirty species of arenaceous foraminifera have been discovered in samples of Arbuckle, Viola and Chimney Hill limestones from the Arbuckle Mountain region. The species belong to the described families Astrorhizidae, Rhizamminidae, Saccamminidae, Hyperamminidae, Ammodiscidae and the new family Stegnamminidae. A new subfamily is erected to include the two new genera, Stegnammina and Raibosammina. A new genus Colonammina assigned to family Saccamminidae is recognized. Altogether three new genera and twenty-seven new species are described. The cementing material of these foraminifera has apparently been replaced by silica and they were removed, in a perfect state of preservation, from the hard crystalline limestone by dissolving it in hydrochloric acid.